Characterisation of carbon fibre (Cf) - Poly Ether Ketone (PEK) composite powders for laser sintering. (July 2019) - Chen, Binling; Berretta, Silvia; Davies, Richard; Ghita, Oana
Abstract: Laser sintering (LS) of composites is an attractive prospect for industries with an interest in complex structures of enhanced mechanical performance. Unfortunately, dry blends of carbon fibre (Cf) and polymeric powders are known to lead to poor mechanical properties. This paper brings evidence that Cf incorporated within the polymer grains (referred in the paper as composite grain powder) can enhance mechanical performance and highlights areas within the powder preparation stages where careful powder examination is critical. An in-depth powder analysis was performed on a dry blend of Cf/PEK powder and several composite grain powder grades obtained from milling, both at 30 wt% of Cf. The results showed that characterisation of the milling fraction is very important and only certain composite grain grades maintain expected powder properties for LS as well as wt% of Cf. The SEM images of laser sintered films provided a clear insight into what happens in the laser sintering of dry blends versus composite grain powders. The complex moduli (E*) obtained from the DMTA tests presented an increase in the samples manufactured using composite grain powders over the dry blend powder and approximately double values when compared with plain polymer HP3 PEK. Highlights: Carbon fibre (Cf) encapsulated PEK composite grain powders with different particle sizes were prepared. The real Cf content in each of the sieved composite powders was characterized. The Cf encapsulated PEK composite films show enhanced complex moduli (E*) over the dry blend films. Fraction B is the optimum Cf composite powder grade for laser sintering.